INOVASI PERAN PEMERINTAH DESA DALAM KEBIJAKAN PARIWISATA DI KOTA BATU - Amirudin, Akhmad (Department of Public Administration, Universitas Negeri Surabaya, 2017)
This research examine the innovation of village government? roles in tourism policy in Batu Municipality, Batu Municipality is one of the cities in Indonesia whose economic growth is dominated by the tourism sector. Economic growth during 2012-2016 Batu City's economy has shown a marked increase with an average of 6.95 percent but the poverty rate has not shown a significant decline with the number of more than 9,000 people since 2013 to 2016 and the gini ratio in 2015 was recorded at 0,36 points or up from the 2013 figure of 0.31 points. This indicates that the growth of the tourism sector has not been able to be felt by the entire community. this happens because the tourism sector is still dominated by large investors by building artificial tourism (artificial) which involves minimal society, therefore the city government of Batu develop a new approach by optimizing the role of village government in developing the policy village tourism and form of pokdarwis (kelompok sadar wisata (group of tourism awareness)). This research uses qualitative approach, case study research and interactive model analysis from Miles, Huberman and Saldana. The result of the analysis shows that the innovation of the role of village apparatus in developing the new community based tourism destination and the collaboration with pokdarwis has given a new form in tourism policy in Batu Town, the tourist villages developed at the village level are more successful in giving positive influence to the people's welfare as well able to involve massively society.